Stimulation of TM3 Leydig cell proliferation via GABAA receptors: A new role for testicular GABA - Krieger Annette; Thalhammer Andrea; Doepner Richard FG; Geigerseder Christof; Mayerhofer Artur (BMC, 2004)
Abstract The neurotransmitter gamma-aminobutyric acid (GABA) and subtypes of GABA receptors were recently identified in adult testes. Since adult Leydig cells possess both the GABA biosynthetic enzyme glutamate decarboxylase (GAD), as well as GABAA and GABAB receptors, it is possible that GABA may act as auto-/paracrine molecule to regulate Leydig cell function. The present study was aimed to examine effects of GABA, which may include trophic action. This assumption is based on reports pinpointing GABA as regulator of proliferation and differentiation of developing neurons via GABAA receptors. Assuming such a role for the developing testis, we studied whether GABA synthesis and GABA receptors are already present in the postnatal testis, where fetal Leydig cells and, to a much greater extend, cells of the adult Leydig cell lineage proliferate. Immunohistochemistry, RT-PCR, Western blotting and a radioactive enzymatic GAD assay evidenced that fetal Leydig cells of five-six days old rats possess active GAD protein, and that both fetal Leydig cells and cells of the adult Leydig cell lineage possess GABAA receptor subunits. TM3 cells, a proliferating mouse Leydig cell line, which we showed to possess GABAA receptor subunits by RT-PCR, served to study effects of GABA on proliferation. Using a colorimetric proliferation assay and Western Blotting for proliferating cell nuclear antigen (PCNA) we demonstrated that GABA or the GABAA agonist isoguvacine significantly increased TM3 cell number and PCNA content in TM3 cells. These effects were blocked by the GABAA antagonist bicuculline, implying a role for GABAA receptors. In conclusion, GABA increases proliferation of TM3 Leydig cells via GABAA receptor activation and proliferating Leydig cells in the postnatal rodent testis bear a GABAergic system. Thus testicular GABA may play an as yet unrecognized role in the development of Leydig cells during the differentiation of the testicular interstitial compartment.